Physical properties of cement composite with monoethanolamine - Lee, Sangsoo; Jeon, Eunyeong; Lee, Jeongtaek (Edelweiss Applied Science and Technology, 2024)
This study analyzed the fluidity, air content, flexural strength, compressive strength and carbon dioxide adsorption performance of cement, furnace slag and fly ash-based cement composite using appropriate substitution values of MEA derived from preliminary experiments. Fluidity and air content were found to increase as the fly ash substitution rate increases. It is believed that the increases are due to the fly ash ball bearing effect in combination with the creation of micropores by MEA. The compressive strength was found to decrease with lower furnace slag substitution ratios. This is believed to have resulted because the Pozzolanic reaction of the fly ash plays a more dominant role in determining the compressive strength than does the latent hydraulic activity of furnace slag as the furnace slag substitution rate is decreased. It is determined that the compressive strength was reduced because the Pozzolanic reaction reduces the density of the texture and pore structure of the interfacial transition zone. Carbon dioxide values increase as the furnace slag substitution rate was increased.